Standardization and clinical applicability of sensorineural acuity level test - Mary John (Journal of All India Institute of Speech and Hearing, 1970)
Bone conduction testing is one of the most important tests in hearing evaluation. In the differential diagnosis of hearing impairment the measurement of pure tone bone conductionthresholds is sought as a primary means of establishing the existence and amount of sensorineural component of the hearing loss. The testing by bone conduction became extensive inclinical procedures after Wheatstone in 1827.